Tratamiento prostésico de un caso de displasia ectodérmica hipohidrótica - Dairo Javier Marín-Zuluaga (Universidad de Antioquia, 2000)
Anodontia is an entity associated to diferent kind 01syndromes. This article reports the treatment using complete dentures.of a six years child who doesn 'tha ve neither deciduous orpermanent dentition, beca use 01an Hypohidrotic Ectodermal Dysplasia. Variations to theconventional technique lorcomplete dentures ha ve been introduced, someol them reported in the litereture, and othersuch a resultoleither personal and other investigators ,research.